2022
DOI: 10.1093/toxsci/kfac067
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Toxicological Assessment of A Novel siRNA, SLN360, Targeting Elevated Lipoprotein (a) in Cardiovascular Disease

Abstract: SLN360 is a liver-targeted N-acetyl galactosamine (GalNAc)-conjugated siRNA with a promising profile for addressing Lp(a)-related cardiovascular risk. Here we describe the findings from key pre-clinical safety studies. In vitro, SLN360 specifically reduced LPA expression in primary human hepatocytes with no relevant off-target effects. In rats, 10mg/kg subcutaneous SLN360 was distributed specifically to the liver and kidney (peak 126 or 246 mg/g tissue at 6h respectively), with <1% of pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…In an in vivo study using cynomolgus monkeys, it was found that SLN360 caused up to 95% reduction in serum Lp(a) concentration and, importantly, this effect was long-lasting [63]. Toxicological analyzes, both in vitro and in vivo, showed satisfactory safety of using SLN360 [64].…”
Section: Sln360mentioning
confidence: 98%
“…In an in vivo study using cynomolgus monkeys, it was found that SLN360 caused up to 95% reduction in serum Lp(a) concentration and, importantly, this effect was long-lasting [63]. Toxicological analyzes, both in vitro and in vivo, showed satisfactory safety of using SLN360 [64].…”
Section: Sln360mentioning
confidence: 98%
“…This innovative siRNA targets the LPA mRNA and consequently lowers apo(a) expression [ 14 , 181 ]. It consists of a 19-mer siRNA modified with GalNAc [ 14 , 181 , 182 ].…”
Section: Reduction Of Lp(a) By Rna-based Therapeuticsmentioning
confidence: 99%
“…Various subcutaneous doses ranging from 0.1 to 9.0 mg/kg were administered, with the minimally effective dose identified as 0.3 mg/kg. Importantly, no evidence of inflammation, cytokine production, complement stimulation, or micronucleus formation associated with SLN360 use, was found [ 244 , 245 ]. Toxicology studies in rats further supported the tolerability of SLN360 in all doses tested [ 245 ].…”
Section: Molecular Lp(a)-targeting Therapies: In the Heart Of The Pro...mentioning
confidence: 99%
“…Importantly, no evidence of inflammation, cytokine production, complement stimulation, or micronucleus formation associated with SLN360 use, was found [ 244 , 245 ]. Toxicology studies in rats further supported the tolerability of SLN360 in all doses tested [ 245 ].…”
Section: Molecular Lp(a)-targeting Therapies: In the Heart Of The Pro...mentioning
confidence: 99%
See 1 more Smart Citation